Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Produk-Produk Online Pada Marketplace Bukalapak: Studi Kasus Pada Followers Instagram Bukalapak - Al’amudi, Ivana Supi; Darma, Surya; Nursaimatussaddiya, Nursaimatussaddiya; Sarwoto, Sarwoto (Economic Development Progress, 2024)
This study aims to determine the factors that influence the decision to purchase online products on the Bukalapak Marketplace (Case Study on Bukalapak Instagram Followers). The research method used is a quantitative method using SPSS version 25.00. The results were collected from the results of distributing questionnaires to bukalapak users as many as 100 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing, namely the T test. The results of SPSS in this study are the price variable (X1) affects the purchasing decision variable (Y ), Brand image variable (X2) has no effect on purchasing decision variables (Y), product quality (X3) affects purchasing decisions (Y) and Product quality (X3) is the most dominant variable influencing purchasing decisions (Y).